H49 Effectivness of pharmacotherapy in huntington's disease. (September 2018) - Doleckova, Kristyna; Dusek, Pavel; Konvalinkova, Romana; Roth, Jan; Klempir, Jiri
Abstract : The potentional benefit of symptomatic treatment of motor impairment in Huntington´s disease (HD) is still discussed. The aim of this study was to find out the effect of medication at different stages of this disease, In our Registry database containing 309 examinations of patients (aged 50.3±13.4 years, disease duration 9.13±3.51 years, CAG ranging from 40 to 70 repeats) was analysed usage of different drugs in comparison. To objectify performance of patients, Unified Huntington´s Disease Rating Scale – total motor score, motor scale subscores (voluntary, occulomotor, chorea, dystonia, rigidity), Total Functional Capacity and Functional Assessment were used. Risperidone was the most used medication with 154 assessements with this treatment and 155 without. Other preparates with the strongest representation were amantadine (97:212 events), clonazepam (56:253), tiapride (49:260), tetrabenazine (13:296) and haloperidol (11:298). Statistically (Mann-Whitney U-test) were compared patients with and without particular medical treatement, with only significant results in patients with clonazepam therapy, who had only significantly higher voluntary motor subscore (p<0.001). Additionally, we performed a linear model using ordinary least squares calculation to count for the effect of disease progression (age, disease duration, CAG repeats). The difference in voluntary motor subscore was independent on the disease progression. Although a longitudinal study should be performed to prove causality of clonazepam, caution should be used when prescribing clonazepam in HD.